Effect of serum IL-1beta of PCSO-524 and firocoxib in dogs undergoing medial patellar luxation repair - Sararat Kongwut (2018)
Thirty client-owned Pomeranians, between one and seven years old that had grade-three medial patellar luxation, were enrolled in this experiment. The dogs did not have other diseases. All the dogs received the same physical and clinical orthopaedic examinations, as well as the peak vertical force gait analysis, radiographic examination for assessment of bone deformities. Then, blood was collected from each dog for evaluation of complete blood counts (CBCs), blood chemistry and biomarker assays (IL-1β) before surgery. After surgery to correct their medial patellar luxations, they were divided into three groups by random sampling. The first group received only Firocoxib (5 mg/kg once daily). The second group received only PCSO-524 (10 mg/kg, twice daily). The third group received Firocoxib (5 mg/kg, once daily) combined with PCSO-524 (10 mg/kg, twice daily). Treatment finished at the end of the second week. Every dog received a blood collection before surgery and at days one, five and 14 after surgery. IL-1β concentrations in serum were determined by commercially available canine ELISA kits. The result was that two treatments (Firocoxib only and Firocoxib combined with PCSO-524) can reduce the serum IL-1β level by day 14 after the surgical correction of patellar luxation. However, the group that received PCSO-524 did not have significantly decreased of serum IL-1β, but it had a slower decline of the serum IL-1β level. We concluded that PCSO-524 did not diminish serum IL-1β levels as good as NSAID in case of post-surgical correction of patellar luxation. For the further study, we recommend to increase dose of PCSO-524 and period of treatment before surgery in other condition that causes acute inflammation. Maybe the extraction of active ingredients in PCSO-524 is necessary. Moreover, we suggest increasing the sample size for showing the more significance and accurate results.